2002
DOI: 10.1016/s1201-9712(02)90138-4
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of treatment of Buruli ulcer with rifampin and dapsone

Abstract: Results of this study indicate that larger studies of antimycobacterial therapy of BU are warranted and can be successfully undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…In an attempt to establish the diagnosis by punch biopsies, acid-fast bacilli were identified and cultured for four patients. Cultures of lesions are infrequently positive, and this figure is consistent with that reported by others (9). It may be possible to achieve more positive diagnoses by using a PCR for M. ulcerans DNA, which was not available to us at the time of the study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In an attempt to establish the diagnosis by punch biopsies, acid-fast bacilli were identified and cultured for four patients. Cultures of lesions are infrequently positive, and this figure is consistent with that reported by others (9). It may be possible to achieve more positive diagnoses by using a PCR for M. ulcerans DNA, which was not available to us at the time of the study.…”
Section: Discussionsupporting
confidence: 88%
“…This expensive treatment is not available in most areas where the disease is endemic (3). Chemotherapy with antimicrobial agents has been used (11), but the only published controlled trials suggest that clofazamine is ineffective (19) and that rifampin and dapsone combined have limited efficacy (9). Many types of topical treatment have been reported, but none has been subjected to the rigors of a controlled clinical trial (2).…”
mentioning
confidence: 99%
“…In vitro, a number of agents (including clarithromycin, several quinolones, and rifampin) are active, but few clinical studies have been done. A pilot study using dapsone plus rifampin in Côte d'Ivoire showed modest effect [41].…”
Section: Buruli Ulcer (Mycobacterium Ulcerans)mentioning
confidence: 99%
“…In a mouse footpad model of M. ulcerans infection, treatment with a combination of rifampin and amikacin has yielded promising results (7), and clinical trials with combinations of antibiotics are currently in progress (11). Monitoring of the response to chemotherapy may represent another useful application of the IS2404 TaqMan assay.…”
Section: Vol 41 2003mentioning
confidence: 99%